HARMFUL CONDITIONS ON THE DENTAL STATUS OF POULTRY FARM WORKERS - T. Pupin; O. Kardashevska (Ukrainian Medical Stomatological Academy, 2016)
The results of dental examination of 120 poultry farm workers of Zboryv city are displayed in the article. Examination determined the dental status of the patients, decay intensity of hard tissues of teeth, oral hygiene level, prevalence rate of non-carious diseases of teeth and inflammatory periodontal diseases level, condition of the oral mucosa depending on the length of work on the poultry farm. Prevalence of dentition and periodontal tissues diseases in poultry farm employees has been identified, it requires special attention of working conditions and its health effect. Improvement of dental care for poultry farm staff who meets some groups of harmful factors becomes so important in this regard. Impact of harmful production factors on oral health status of poultry factories employees. The article represents results of dental examination of 120 poultry factory employees. According to examination results the dental status of the patients has been indicated as well as decay intensity of hard tissues of teeth, oral hygiene level, prevalence of non-carious teeth diseases and periodontal inflammatory rate, oral mucosa condition depending on length of work at the poultry farm. Due to intensive development of agriculture, it becomes important to study the influence of harmful and health related risk factors at the work place. Harmful work conditions influence onto formation of different pathological processes throughout the body. One among rapidly developing branches of industry in agriculture is poultry. The high concentration of poultry and its maintenance leads to appearance of some harmful factors linked with industrial poultry. Producing poultry is related to high concentrations of dust in the air, dust structure is complex, includes various harmful gases, bacteria and fungy. However, many indicators exceed MAC PDU installed GOST air working area. Continuous exposure to complex producing factors along with the deterioration of workers health may lead to pathological changes in the oral mucosa (CMO), periodontal diseases, etc. Extremely high prevalence of periodontal diseases of oral system among staff requires increasing attention to the conditions and employment rights and its impact on health. In this regard, dental care improvement for the farm employees who meets harmful conditions becomes important. Researches evaluated hygienic indexes of working areas by laboratory method. Indicated that the dust in areas where birds are kept is mixed. It consists mainly of organic particles as feathers, dandruff and excrement of birds. At the same time, there have been detected some particles originated from plants, animals and minerals,it must be parts of the feed, and silicon dioxide. Compaction of dust is accompanied with such processes as catching and poultry cull, cleaning industrial equipment, feeding. These processes lead to increase of dust amount by several times and it reaches 43.2 mg / cu. m (at MAC 6 mg / cu. m). In addition, the total amount of dust in poultry buildings depends on the capacity and efficiency of ventilation as well as of the type of equipment. Presence of harmful gases (ammonia, hydrogen sulfide, carbon dioxide) in the air of poultry farm associates with the activity of poultry and decomposition of the organic substances (manure, bedding, feed, etc.). Indicators of gaseous impurities concentration significantly increases during cold and transitional seasons of the year. The source of fungal and bacterial pollution of the working area still the same it is birds. Tests show large number of semination of the air within poultry buildings where average number is 1950, and the number of mixed colonies are 1460 CFU. In addition, poultry production is noisy. In some areas through poultry farm, noise level, in some cases, reaches the top of the scale up to 56-85 dBA. Researches on production microclimate discovered that there are areas where poultry is kept, with deviation from the allowable temperature, relative humidity and air velocity. The main aim of research is to evaluate the dental status of the poultry employees. Thus, examining complex found high prevalence of diseases of dental hard tissues and decay, inflammatory diseases of periodontal tissues, red lips and oral mucosa in comparing with control group. Such oral mucosa lesions were allergic in origin. In accordance with medical history there are 69% workers at poultry farms are chronic comorbidities in the form of allergic rhinitis, rhino-sinusitis, skin allergic dermatitis, allergic bronchitis and chronic asthma. These data indicate a significant harmful impact of poultry production onto oral health of workers. The development of algorithms for diagnosis, prevention and treatment of dental diseases for this category of workers are considered as necessary.